General Method for Large‐Area Films of Carbon Nanomaterials and Application of a Self‐Assembled Carbon Nanotube Film as a High‐Performance Electrode Material for an All‐Solid‐State Supercapacitor. (21st March 2017) - Song, Li; Cao, Xuebo; Li, Lei; Wang, Qiaodi; Ye, Huating; Gu, Li; Mao, Changjie; Song, Jiming; Zhang, Shengyi; Niu, Helin
Abstract : Rational assembly of carbon nanostructures into large‐area films is a key step to realize their applications in ubiquitous electronics and energy devices. Here, a self‐assembly methodology is devised to organize diverse carbon nanostructures (nanotubes, dots, microspheres, etc.) into homogeneous films with potentially infinite lateral dimensions. On the basis of studies of the redox reactions in the systems and the structures of films, the spontaneous deposition of carbon nanostructures onto the surface of the copper substrate is found to be driven by the electrical double layer between copper and solution. As a notable example, the as‐assembled multiwalled carbon nanotube (MWCNT) films display exceptional properties. They are a promising material for flexible electronics with superior electrical and mechanical compliance characteristics. Finally, two kinds of all‐solid‐state supercapacitors based on the self‐assembled MWCNT films are fabricated. The supercapacitor using carbon cloth as the current collector delivers an energy density of 3.5 Wh kg −1 and a power density of 28.1 kW kg −1, which are comparable with the state‐of‐the‐art supercapacitors fabricated by the costly single‐walled carbon nanotubes and arrays. The supercapacitor free of foreign current collector is ultrathin and shows impressive volumetric energy density (0.58 mWh cm −3 ) and power density (0.39 W cm −3 ) too. Abstract : A general methodology for the manufacture of macroscopic films of nanostructured carbon is demonstrated. The method is based on a solution assembly mechanism mediated by electrical double layer. 1D, 2D, or 3D carbon nanostructures can be organized into free‐standing films with potential infinite lateral dimensions. Moreover, an all‐solid‐state supercapacitor fabricated using as‐assembled multiwalled carbon nanotube (CNT) films exhibits performances comparable to those based on single‐walled CNTs.